2009
DOI: 10.1021/bi900246h
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatinization as a Potential Mechanism of Nickel-Induced Carcinogenesis

Abstract: Epigenetics refers to heritable patterns of gene expression that do not depend on alterations of the genomic DNA sequence. Nickel compounds have demonstrated carcinogenicity without any associated mutagenesis, suggesting that its mechanism of carcinogenesis is epigenetic in nature. One such potential mechanism is the heterochromatinization of chromatin within a region of the genome containing a gene sequence, inhibiting any further molecular interactions with that underlying gene sequence and effectively inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 30 publications
(43 reference statements)
2
51
1
Order By: Relevance
“…These results suggest a loss of CTCF-mediated insulation function as a potential reason for domain disruption and spreading. Because epigenetic alterations are believed to be the basis of Niinduced cancers (14,16), our finding of H3K9me2 domain disruption by Ni and a potential role for CTCF in maintaining H3K9me2 domains will have profound implications in understanding the process of carcinogenesis.…”
Section: Significancementioning
confidence: 96%
See 3 more Smart Citations
“…These results suggest a loss of CTCF-mediated insulation function as a potential reason for domain disruption and spreading. Because epigenetic alterations are believed to be the basis of Niinduced cancers (14,16), our finding of H3K9me2 domain disruption by Ni and a potential role for CTCF in maintaining H3K9me2 domains will have profound implications in understanding the process of carcinogenesis.…”
Section: Significancementioning
confidence: 96%
“…Intriguingly, Ni-induced silencing of gpt and increased H3K9me2 levels occurred only when the transgene was integrated near a heterochromatic region (13,14,21). This suggests that Ni could induce H3K9me2 spreading.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies have reported histone hypoacetylation, increased methylation/ubiquitination of histones Ke et al, 2006;Li et al, 2009) and changes in the chromatin stationary structure (Ellen et al, 2009) in response to nickel and cobalt exposure. These studies also pointed to hypoxia and ROSs generation as causes of decreased acetyl-CoA, a substrate for histone acetylation due to heavy metal exposure .…”
mentioning
confidence: 99%